Lean User Experience (Lean UX) Approach in the Redesign of the SOBAT BPS Application - Migunani Puspita Eugenia; Lutfi Rahmatuti Maghfiroh (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
SOBAT BPS is a service provided by BPS to be used by partners and prospective partners of BPS throughout Indonesia. Alongside the utilization of the SOBAT BPS application, user reviews and assessments become significant elements in measuring the quality and success of this application. Feedback obtained from these assessments indicates that a redesign of the SOBAT BPS application is necessary to provide a better user experience. Prior to redesigning the SOBAT BPS application, a preliminary survey was conducted to understand user perceptions of the current system using heuristic evaluation and the user experience questionnaire (UEQ). Based on the preliminary survey results, there are issues related to the implementation of heuristic principles in the SOBAT BPS application, and only the UEQ stimulation scale received a good ranking. Therefore, the aim of this research is to redesign the SOBAT BPS application using the Lean UX method and to evaluate the redesigned results using heuristic evaluation and UEQ. The evaluation results of the redesigned SOBAT BPS application indicate that the redesign is superior to the current SOBAT BPS application.